Motivasi Pelayanan Publik dalam Peningkatan Kinerja Pelayanan di Kantor Camat Padang Timur - Nofal Wiska; Asrinaldi Asrinaldi; Aidinil Zetra (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2022)
In the implementation of regional autonomy, the paradigm of public service should shift from services that are centralized to services that focus more on customer-driven government. But in reality, the practice of public services in many areas is unsatisfactory for the community. The causes of public services still have weaknesses, namely less responsive, less informative, less accessible, less coordinated, bureaucratic, less willing to listen to public complaints, and inefficiency. Another factor is the low motivation for public services. For Padang City, one of the sub-districts that has excellent service is the East Padang sub-district. However, the service process at this sub-district office has fluctuated. Many people complain about the service pattern, including the room that is not representative in carrying out public services. This research uses descriptive qualitative research. To obtain data in accordance with the research focus, the researchers conducted interviews, observations and documentation. Then the data obtained were analyzed using interactive analysis methods. In Padang Timur District, the aspects of public service motivation that are practiced are giving rewards and punishments, conducting coaching and training, and applying transformational leadership. To achieve optimal public services, it is necessary to have a Public Service Motivation that prioritizes competition, competence and consistency.